Pleistocene demographic histories dominate contemporary genomic diversity in a continental radiation of Himalayan–Hengduan songbirds - Yadan Liu; Chih-Ming Hung; Yunrui He; Fei Wu; Dao Yan; Gang Song; Feng Dong (Proceedings of the National Academy of Sciences, 2026)
Genetic diversity, the fundamental substrate for evolutionary potential, is declining globally at unprecedented rates. Yet the mechanisms governing its distribution across species remain poorly understood, with competing hypotheses emphasizing either historical demography or contemporary ecological constraints. This debate limits our capacity to predict species' responses to environmental change. Here, based on systematic sampling and a unified analytical pipeline, we de novo assembled genomes for 120 songbird species breeding in the Himalayas–Hengduan Mountains (HHMs) and conducted population genomic analysis to examine the drivers of their genomic diversity. We observed a 6.5-fold variation in genome-wide heterogeneity and a 16.4-fold variation nucleotide diversity across species. Notably, these measures of genomic diversity showed no correlation with recent population dynamics, current population size, or other contemporary factors—such as elevational distribution, or life-history traits. Instead, historical demography strongly predicted genetic diversity, with ancestral population size during the late Pleistocene emerging as the sole correlate: Larger ancestral sizes consistently coincided with higher diversity. These findings underscore the critical influence of historical demography on contemporary genetic diversity in natural populations—an insight essential for designing effective conservation strategies.